Making Ireland British, 1580-1650 - Canny, Nicholas P. (Oxford University Press, 2001)
This is a comprehensive study of the plantations that were attempted in Ireland during the years 1580-1650. It examines the arguments advanced by successive political figures for a plantation policy, and the responses which this policy elicited.